Analysis of Coagulation Abnormality in Patients with Multiple Myeloma and Its Clinical Significance. (20th June 2022) - Pan, Pengji; Liu, Junxia
Abstract : Objective . To analyze the abnormal changes of coagulation indexes in patients with multiple myeloma (MM) and their clinical significance on prognosis. Methods . Among 80 patients with MM, there were 24 patients of light chain type, 36 patients of IgG type, and 20 patients of IgA type. In the same period, 30 healthy people were in the control group. The laboratory indexes such as plasma prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (FIB), thromboplastin time (TT), D-dimer (D-D), and platelet (PLT) were detected and compared. The prognosis of MM patients was followed up, and the effects of various coagulation indexes on the prognosis of MM were analyzed by single-factor and multifactor analyses. Results . The PT and APTT of IgG and IgA groups were longer than those of the control group and the light chain group (P < 0.05 ), but there was no significant difference between the IgG group and the IgA group, the control group, and the light chain group. There was no significant difference in FIB values among the four groups (P > 0.05 ). The D-D content in the light chain group was higher than that in the control group, the IgG group, and the IgA group (P < 0.05 ). During the follow-up period, of 80 MM patients, 61 patients survived and 19 patients died. Univariate analysis showed that APTT, PT, and D-D were the factors affecting the prognosis of MM patients, and the differences were statistically significant (P < 0.05 ). Multivariate analysis showed that PT was an independent factor affecting the prognosis of MM patients (P < 0.05 ). Discussion . Patients with MM have clotting abnormalities. Patients with IgA and IgG type MM have a longer clotting time than patients with other types of MM, and patients with light-chain type MM have higher D-D content and are more prone to thrombosis. PT is an independent factor affecting the prognosis of MM patients, and analysis of coagulation abnormalities is important for evaluating the prognosis of patients.